Analisis Aspek Kriminologi dalam Tindak Pidana Pelanggaran Hak Merek sebagai Kejahatan Ekonomi yang Mengganggu Perlindungan Hukum dan Keadilan Sosial - Moh Zulham Sidiq (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
A brand is one of the most valuable intellectual assets in the business sector, serving not only as a product identity but also as a reflection of reputation and quality. However, the increasing phenomenon of brand infringement indicates the urgent need for stronger and more effective legal protection. Brand infringement brings various negative consequences, including loss of consumer trust, unfair competition, and significant financial losses for brand owners. This study aims to analyze brand infringement from a criminological perspective, identify causal factors, and evaluate the role of law in addressing such violations. The research employs normative legal methods through analysis of statutory regulations, legal and criminological theories, and a literature-based approach using secondary data obtained from books, journals, and legal documents. The findings reveal that criminology provides relevant insights through theories such as Rational Choice Theory, which explains that perpetrators calculate the risks and benefits before committing the violation, and Anomie Strain Theory, which highlights how the inability to achieve economic or social goals legally can drive individuals or groups to commit brand infringement. The classification of violations includes imitation, counterfeiting, misuse, and unlawful exploitation of brand rights. Several causal factors were identified, including weak legal supervision, limited enforcement, and the high consumer demand for cheaper counterfeit products. Furthermore, the study underlines the essential role of the criminal justice system in addressing brand infringement through the enforcement of criminal, civil, and administrative sanctions as regulated under Law Number 20 of 2016 on Trademarks and Geographical Indications. In conclusion, brand infringement is not merely a legal issue but also a criminological problem that requires comprehensive handling through effective law enforcement, stronger supervision, and increased public awareness to protect intellectual property and ensure fair business practices.